Density of bacteria in Limnodrilus sp. culture fertilized by fermented chicken manure - Y. Hadiroseyani; . Nurjariah; D. Wahjuningrum (Jurnal Akuakultur Indonesia)
Culture of Limnodrilus sp. is now developed to control continuously supply.  Culture medium of Limnodrilus sp. consists of mud and organic waste.  Routinely fertilization is needed to keep enough nutrition.  One of organic fertilizer used in Limnodrilus sp. culture is chicken manure.  This fertilizer contains high levels of N, low-priced and easy to obtain.  This study was conducted to determine Limnodrilus sp. density in the substrate fertilizer by fermented chicken manure and Limnodrilus sp. growth. Mud and chicken manure in ratio of 1:1 was applied to container of 100×20×15 cm3.  Fertilization was carried out 2 times daily at the dose of chicken manure 130, 160 and 190 g/container.  The result of study showed that density of bacteria tends to decrease during experiment.  Highest density (11,948 individuals/m2) and biomass (14.65 g/ m2) of bacteria was obtained by 190 g of chicken manure fertilization.